Recovery of pure lithium phosphate from sulfuric acid leaching solutions of spent LiFePO4 batteries by solvent extraction and chemical precipitation : Recovery of pure lithium phosphate from spent LiFePO4 batteries (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
With the increasing use of electric vehicles, the demand for lithium iron phosphate (LiFePO4) batteries has sharply increased. Hence, the recycling of metals from these batteries after end-of-life is necessary. In this study, a hydrometallurgical process for recovering lithium phosphate from spent LiFePO4 batteries was developed. The effect of parameters on the recovery process consisting of leaching, solvent extraction, and precipitation were investigated. The addition of H2O2 to the H2SO4 solution was ineffective for the selective leaching of Li(I) over iron. The results showed that Li(I) and iron were completely dissolved by 1.5 mol/L H2SO4, 100 g/L pulp density at 25oC for 60 mins and 300 rpm. After oxidizing the Fe(II) in the leaching solution by adding H2O2, Fe(III) was completely separated from the solution by five stages of cross-current extraction with 1.0 mol/L D2EHPA at room temperature. The loaded Fe(III) was successfully stripped by four stages of cross-current stripping with 50% (v/v) aqua regia solution. Finally, most of Li(I) was recovered by precipitation of lithium phosphate from the iron free raffinate by maintaining solution pH at 11 and at 95oC for 30 mins. The optimum conditions for the complete dissolution of LiFePO4 batteries by sulfuric acid solution and for the separation of iron and lithium ions from the leaching solutions were obtained. A hydrometallurgical process was proposed for the recovery of pure lithium phosphate from spent LiFePO4 batteries.
Keywords: spent LiFePO4 battery; recovery, solvent extraction; precipitation; lithium